Acute abdomen in the centanary patient, mesh migration into the sigmoid colon after laparoscopic inguinal hernia repair (TAPP): A case report and review of literature - Fajardo, Roosevelt (Int J Surg Case Rep, 2019)
BACKGROUND: The complications induced by mesh, such as foreign body reaction, deep-seated infection, mesh migration and perforation into viscera, have been reported sporadically. Colon erosion and penetration by laparoscopic transabdominal preperitoneal (TAPP) inguinal hernia repair mesh can possibly cause perforation of the colon with acute abdomen. CASE PRESENTATION: A 100-year-old male, who underwent 4 years ago TAPP repair of left inguinal, presented to the emergency department with acute abdomen due to chronic mesh penetration into the sigmoid colon, the migrating mesh generated a free wall perforation with generalized fecal peritonitis. DISCUSSION: Tailoring the mesh, appropriate suture placement and adherence to principles of antisepsis during hernia repair surgery are crucial in avoiding longterm mesh-related complications. CONCLUSION: TAPP is a safe procedure for treat groin hernias, unless, mesh complications like foreign body reaction, deep-seated infection, mesh migration and perforation.